The border between them violence and reconciliation on the Kansas-Missouri line - Neely, Jeremy, 1975- (University of Missouri Press, 2007)
"Jeremy Neely recounts the exploits of John Brown, William Quantrill, and other notorious guerrillas, as well as the stories of everyday people who lived through the conflict that marked the terrible first act of the American Civil War. He then examines how emancipation, industrialization, and immigration eventually eroded wartime divisions"--Provided by publisher.